Validation of a Diagnostic Microarray for Human Papillomavirus: Coverage of 102 Genotypes - Sarah Tuttleton Arron; Peter Skewes-Cox; Phong H. Do; Eric Dybbro; Maria Da Costa; Joel M. Palefsky; Joseph L. DeRisi (Journal of Nucleic Acids)
Papillomaviruses have been implicated in a variety of human diseases ranging from common warts to invasive carcinoma of the anogenital mucosa. Existing assays for genotyping human papillomavirus are restricted to a small number of types. Here, we present a comprehensive, accurate microarray strategy for detection and genotyping of 102 human papillomavirus types and validate its use in a panel of 91 anal swabs. This array has equal performance to traditional dot blot analysis with the benefits of added genotype coverage and the ability to calibrate readout over a range of sensitivity or specificity values.